Nationwide population-based study of prevalence and trend of borderline ovarian tumors in the Republic of Korea - Yung-Taek Ouh (Nature Portfolio, 2021)
Abstract Borderline ovarian tumors (BOTs) represent noninvasive tumors with uncertain malignant potential. They have a favorable prognosis although they can also recur or be fatal. There are limited population-based data on BOTs, its incidence and surgical treatment approach. We sought to analyze these trends in South Korea between 2014 and 2018. Data from patients diagnosed with BOT between 2014 and 2018 were obtained from the Health Insurance Review and Assessment Service/National Inpatient Sample in South Korea. Treatment was analyzed by using codes including adnexal surgery with or without hysterectomy. Data from 4,636,542 women were entered into the database between 2014 and 2018. Data from 5,109 women with BOT, and 537 women with surgery were extracted for analysis. The highest prevalence of BOT occurred in women 40–44 years old. In logistic regression analysis, age was significantly correlated with the prevalence of BOT (p < 0.05). The prevalence of BOT was lower in individuals over 50 than it was in those under 50 years (odds ratio (OR), 0.400 in 2014; OR, 0.457 in 2015; OR, 0.419 in 2016; OR, 0.355 in 2017; OR, 0.347 in 2018). The prevalence of BOT varies significantly with age, and is most common in women in their 40 s.